Komunikasi Dalam Transformasi Budaya Perusahaan Terhadap Karyawan - lestari, Julia; lestari, Sarwendah tri; ardiningrum, Anindya (Al Makki Publisher, 2023)
In advancing the company, communication is very important for the running of a company the goals that have been set. Communication will run effectively if the message is well received. In a company there are many diverse employee cultures, inseperable from the role of foreigners in running the company. Instilling values from various cultures has differences in running a company. This study shows the role of corporate culture in increasing internal communication that changes the habits of employees with the role of culture in corporate transformation. The results of workplace communication research are significant because they increase employee morale, engagement, productivity, and satisfaction. Additionally effective workplace communication helps drive better outcomes for individuals, teams and organizations.